CIETAC'S PRACTICE ON THE CISG1 - Dong WU (Nordic Journal of Commercial Law, 2005)
The United Nations Convention on Contracts for the International Sale of Goods (hereinafter referred to as the “ CISG” ) has been regarded as the most important uniform international law for the sale of goods so far. China signed the CISG on 30 September 1981 and deposited its instrument of ratification on 11 December 1986. As of 1 January 1988, the CISG became effective in relation to China. According to the statistics of the World Trade Organization (hereinafter referred to as the “WTO”) issued in April 2005,1China’s exports and imports of merchandise ranked the fourth and third respectively in the world in year 2003. China’s shares in the world total merchandise exports and imports of 2003 were 5.8% and 5.3%, respectively. According to the WTO news,2in 2004 China became the largest merchandise trader in Asia, and the third largest exporter and importer in world merchandise trade. China’s shares in the world total merchandise exports and imports of 2004 respectively reached 6.5% and 5.9%. Evidently, China has been playing a role of increasing importance in the world trade including the trade of goods. Considering that the Contracting States of the CISG include other leading trading states, especially U.S., Germany and the Republic of Korea, which are also the main trade partners of China, the CISG accordingly deserves increasing attention in China from the Chinese side.3 Chinese governmental and judicial bodies have been aware of the importance and the potential influence of the CISG ever since 1987. Before the CISG came into force, the then Ministry of Foreign Trade and Economic Cooperation (the predecessor of the Ministry of Commerce, hereinafter referred to as “MOFTEC” ) issued a notice on 22 January 19874 requesting relevant governmental agencies and companies to make preparation for the forthcoming CISG’s entry into force in relation to China, including but not limited to, to comply with the CISG, to study the CISG, to modify and complete the standard contracts then in use, and to keep aware of the developments of the number of the Contracting States of the CISG. On 4 December 1987, the then MOFTEC further circulated a notice on certain issues meriting attention regarding implementation of the CISG,5 which was shortly endorsed by the Supreme People’s Court on 10 December 1987.6 Since the CISG entered into force, more and more courts and arbitral rulings in which the CISG has been applied have been reported in the past years.7